Prevention of anemia in children through the consumption of a blueberry and quinoa drink enriched with iron as part of a nutritional program - Neglia-Cermeño, Cinthya; Paredes-Díaz, Susana Edita; Soto-Deza, Nancy; Bazán-Cabellos, Jaime; Otiniano, Nélida Milly; Díaz-Ortega, Jorge Luis; Castro-Caracholi, Luz Angélica; Valdiviezo-Campos, Juan Ernesto; Torres, Victoria Ramos; Abanto-Quiroa, Carol; Zariquiey-Rubio, Mariana; Nazario-Terrones, Karla; et al. (Frontiers in Nutrition, 2025)
ObjectiveTo demonstrate the preventive effect against anemia in children by the consumption of a blueberry and quinoa drink enriched with iron as part of a nutritional program.MethodThe nutrition program involved 42 children aged 1 to 6 years. They were the children of workers in an agro-industrial company in the city of Trujillo, where they received a blueberry and quinoa drink enriched with iron in the form of ferric pyrophosphate (BQDEI), the content of which in a 200 mL bottle provides 14 mg of Fe. For children without anemia the dose was 1 bottle per day and for children with mild anemia the dose was 2 bottles per day for a period of 6 months. Educational and demonstration sessions were held for parents or caregivers regarding proper food handling, safe water consumption, the importance of personal hygiene and the benefits of a balanced diet rich in iron. In addition, nutritional status evaluation, parasitosis control and ferritin and hemoglobin measurements were performed at the beginning, third and sixth month during the development of the nutritional program.Results50% of the children with short stature reached normal height, and 80% of the children’s weight/height went from overweight to normal, and these changes were significant. Ferritin concentration in the initial, intermediate and final phases was 40.67 ± 25.20 ng/ml, 49.37 ± 22.41 ng/ml and 54.19 ± 35.38 ng/ml, respectively, showing a significant increase. The hemoglobin concentration was 11.71 ± 0.91 g/dl, 11.83 ± 0.88 g/dl and 11.99 ± 1.03 g/dl, respectively, and the increase was not significant.ConclusionIt was demonstrated that the consumption of BQDEI within a nutritional program contributed to the prevention of anemia in children, by improving hemoglobin and ferritin concentrations. Therefore, it could be implemented in other areas where children are more vulnerable to anemia.